Christine de France Frosne Engraving 17th century - Jean Frosne (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Christine de France Frosne Engraving 17th century. Portrait de Christine de France, Duchesse de Savoie, en buste, de 3/4 dirigé à gauche dans une bordure ovale
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; statue